108. Debating Neolithization from a Mesolithic point of view : The Sado Valley (Portugal) experience - Diniz, Mariana (2021)
In this paper we discuss how the Late Mesolithic Sado Valley hunter-gatherers interacted with the first agropastoralist societies settled in southern Portugal in the course of the second half of the sixth millennium cal BC. The archaeological record available during this period in southern Portugal reflects the presence of two distinct cultural groups. Differences can be detected not only on an economic level but also in settlement patterns, material culture, and symbolic behaviour. By the end of the first quarter of the fifth millennium cal BC, the Sado shell middens seem to have been abandoned, raising the question of how and why these last hunter-gatherers left their traditional territory, since no environmental change is recorded in the area that could explain it. Using chronological information and some Neolithic elements found in the area of the shell middens, we will debate the Neolithization process from a Mesolithic point of view.